(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Medication repositioning and therapeutic switching are other names for drug repurposing. This technique is utilised to separate the innovative therapeutic agents from the FDAapproved medicinal compounds currently being employed in clinical trials. It is regarded as an effective method for creating drug candidates with novel therapeutic or pharmacological features. The unique strategy of drug repositioning is used to boost the success rate of medication development because drug discovery is an expensive, time-consuming, arduous, and extremely risky procedure. This approach has many advantages over the conventional drug discovery procedure, including a shorter drug development timeline, lower costs, higher efficiency, and a lower risk of failure. Breast cancer, which has a high mortality rate, is the most common type of cancer among women globally. One of the biggest obstacles to be overcome in the treatment of breast cancer, medication resistance, is mostly to blame for this high mortality rate. As a result, research has been concentrated on discovering novel therapeutic tools, particularly those that permit a tailored treatment based on patients’ features. In spite of the scientific community’s concern for ensuring the quality of life for cancer patients, researchers are also conscious of the rising expenses associated with cancer therapy, and efforts have been made to find alternatives to the development of new drugs. The multistep, expensive, and time-consuming process of developing new medications has several drawbacks. It involves clinical studies, many of which are unsuccessful in the early stages. Drug repurposing is a method for overcoming these drawbacks. In this research, we described prospective medications for the treatment of breast cancer while taking into account their pharmaco-genomic profile to evaluate the correlation between a patient’s genetic makeup and the treatment they get. This review argues in favour of the necessity of conducting additional basic research in this field in order to examine and advance our understanding of the existing and prospective future treatments for breast cancer.